HADIS DALAM KITAB FIQH KONTEMPORER (Kajian atas Kitab Fiqh al-Sunnah Karya al-Sayyid Sbiq) - Nadhiroh, Wardatun (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2015)
Islamic tradition, well known as Prophetic Hadith, is not only recorded in the primary Hadith Books such as ShahhBukhr, Shahh Muslim, etc, but also in the other books like Historiography and the works about Islamic Law(Fiqh). Fiqh al-Sunnah, the masterpiece of al-Sayyid Sbiqs, is one of the works about Islamic Law that mentionmany hadiths for strengthening the argumentation in it. It has been being reference for many people in the world to studyIslamic Law. It has translated into several different languages. Although the author claimed his argumentation basedon valid hadiths, some of them do not actually fulfill the requirements of the valid hadith. So, this paper discussedabout al-Sayyid Sbiqs applied theory of hadith. Some hadith in his book will be analyzed to prove his theory. Butafter all, Fiqh al-Sunnah must be appreciated well.